Pengaruh Khalwat Tareqat Naqsabandiyah Terhadap Emotional Control dan Kualitas Ibadah pada Santri di Ponpes Darus Shofa Kandis - Lailatul Izzah (Nathiqiyyah, 2022)
The purpose of this study was to find out how the influence of the Seclusion Method in the Naqsyabandiyah Al-Kholidiyah Order has on Emotional Control and the Quality of Worship of the Santri Darus Shofa Kandis Islamic Boarding School. The research method in this research is quantitative with the type of field research. The selection of subjects in this study used purposive sampling with the characteristics of MA and SMK Darus Shofa Islamic Boarding School students aged 15-18 years who participated in Khalwat activities. Based on the results of the F test, it was found that seclusion had an effect on Emotional Control with a result of 69.3% including the good category. This means that seclusion has an influence on emotional control and 58.1% of the seclusion variable affects the quality of worship in a good category. It can be concluded that variable X affects both variables Y1 and Y2